EFEKTIFITAS BABY SPA TERHADAP KUALITAS TIDUR BAYI USIA 3-12 BULAN - Berliana Irianti; Nini Suriani; Riza Febrianti (Maternity and Neonatal : Jurnal Kebidanan, 2025)
Infancy is a golden period for a child's growth and development. During this period, organ maturation occurs in all systems. One of the factors that influences a baby's growth and development is the quality of the baby's sleep. With good quality sleep, the baby's growth and development will be good. One way to make your baby sleep soundly is to do a light massage. Baby SPA is a series of to improve the quality of the baby's sleep. Baby Spa consists of three stages, Baby Massage (massage), Baby Gym (gymnastics), and Baby Swim (swimming). This study aims to determine the effectiveness of Baby SPA on the sleep quality of babies. Research method is pre-experimental with a pretest and posttest research design. Namely looking at the effectiveness of the baby's sleep before and after doing Baby SPA. The sample in the study was 21 babies aged 3-12. The sampling technique uses purposive sampling. The instrument uses a questionnaire. Data processing using SPSS shows that the sleep quality of babies before Baby SPA was carried out by the majority of respondents was poor, with a percentage of 17 respondents (81.0%). and the quality of the baby's sleep after carrying out Baby SPA, the majority of respondents were good, with a percentage of 16 respondents (76.2%). From the results of the Wilcoxon Rank Test statistical test, the p-value = 0.000 < 0.05. So Ha was accepted. It is recommended that midwifery practitioners to improve massage skill for baby.